Verzamelde Tooneelspelen en opstellen-over-tooneel, deel 1-2 - Heijermans, Herman, 1864-1924 (Salt Lake City, UT : Project Gutenberg, 2025)
"Verzamelde Tooneelspelen en opstellen-over-tooneel, deel 1-2" by Herman Heijermans is a collection of theatrical plays and essays on theater written in the early 20th century. This work focuses on Heijermans' views and critiques regarding the state of theater and performance arts, reflecting societal conditions and cultural commentary relevant during his time. The opening of the collection presents the play "Uitkomst," which introduces Thijs Banes, a porter, and his family, showcasing their struggles and interactions in a modest living space in Amsterdam. The dialogue captures the banter between family members and friends, illustrating their everyday lives, discussions about work, and playful exchanges. This initial scene sets the tone for exploring themes such as societal expectations, economic hardship, and the dynamics of familial relationships, providing insight into the struggles of the working class and the impact of their environment on personal aspirations and relationships. (This is an automatically generated summary.)
Uitkomst -- Vreemde jacht -- Ghetto -- De schoone slaapster.
Release date is 2025-02-12
Jeroen Hellingman and the Online Distributed Proofreading Team at https://www.pgdp.net/ for Project Gutenberg (This book was produced from scanned images of public domain material from the Google Books project.)
Keywords: Dutch drama